Social Movements and Digital Activism on Twitter: A Case Study of Development Conflict over the National Strategic Projects (PSN) Rempang Eco City in Batam - Adah, Isti' (Department of Sociology, Universitas Nasional (Indonesia), 2026)
This study investigates the dynamics of social movements and digital activism in the context of the National Strategic Projects (PSN) Rempang Eco City development in Batam. The research applies Habermas's framework of the public sphere, emphasizing its inclusive and participatory nature, and extends this concept to digital platforms. The emergence of cyberspace has transformed traditional public spheres, enabling various societal actors to communicate and express dissent beyond spatial and temporal limitations. The Rempang Eco City project is examined as a case of agrarian conflict, highlighting the tensions between state-driven economic initiatives and the territorial rights of local communities. As of 2024, the issue remains prominent and widely discussed, with local disputes gaining visibility through digital media and contributing to the formation of counter-narratives. The study employs a qualitative netnographic approach and utilizes Social Network Analysis (SNA) to analyze Twitter (X) data collected from September 8 to 18, 2023. The analysis includes public sentiment, trending hashtags, identification of key actors, and the progression of online discourse. The results indicate that digital activism on Twitter has played a significant role in social mobilization related to the Rempang conflict. The SNA findings show that 65% of the networked conversations opposed residential displacement and criticized the reported use of force by authorities, demonstrating the effectiveness of digital platforms in shaping public opinion and supporting collective action.